Gonado-Somatic Index of Gerres oblongus (Cuvier) from Mithbav estuary, Sindhudurg district, Maharashtra, India - Yeragi SS; Yeragi SG (International Journal of Life Sciences, 2015)
Gonado-Somatic Index (GSI) of Gerres oblongus (Cuvier) ranged from 0.3 to 1.6 in male and 0.8 to 3.9 in female and seen high peak in the month of June-July in both the sexes. During the present investigation the higher values of GSI were observed from May to July which ranges between o.9 to 1.4 in the first year and 1.1 to 1.6 in second year for males and 1.9 to 3.8 in the first and 2.4 to 3.9 in the second year for females. Therefore, it was noticed that the fish spawned once in a year with one spawning peak in the month of June-July as indicated by the Gonado-Somatic Index values.